Expression of α TNF in Some Organs of Rabbits Treated with Aflatoxin B1 - Fadia Falah Hassan (Journal of Global Pharma Technology, 2018)
Our study was designed to detect the effect of aflatoxin B1 in liver, kidney and spleen of New Zealand White rabbits and investigate the role of α TNF in aflatoxin B1-induced the same organs toxicity. Histopathological study showed various pathological effects of rabbit’s organs treated with 0.3 mg/kg body weight intraperitoneally with aflatoxin B1 in comparing with control animals. Alpha TNF was used as a marker for immunohistochemically study, results clarified that it was no expression in control animals (score =0) while results of animals treated with 0.3 mg/kg body weight intraperitoneally showed that liver was the most susceptible organs whereas the expression was severe (score =4), strong (score =3) and moderate (score =2) in liver, kidney and spleen respectively.Keywords: Aflatoxin B1, Histopathology, Immunohistochemistry, α TNF.